Genetic investigation and characterization of killer toxins secreted by non-Saccharomyces yeasts - Mehlomakulu, Ngwekazi Nwabisa (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.